Construction of Recombinant Escherichia coli Strain – Producer of Basic Subunit of Toxin-Coregulated Pilus of Adhesion (TCPA) of Vibrio cholerae Biovar El Tor - E. V. Klavdienko; I. V. Tuchkov; T. A. Polunina; N. P. Guseva; N. I. Smirnova (Проблемы особо опасных инфекций, 2017)
Objective of the study is to construct recombinant E. coli strain – producer of TcpA protein of cholera agent El Tor, carrying tcpACIRS gene in its genome, and use the strains for antigen production. Materials and methods. Utilized was non-toxigenic genovariant strain of Vibrio cholerae biovar El Tor from the “State Collection of Pathogenic Bacteria” at the premises of RusRAPI “Microbe”, as well as commercial E. coli strains and plasmids for cloning (Invitrogen, USA). Chromosomal DNA from V. cholerae cells was extracted using Charge Smitch gDNA Mini Bacteria Kit applying nucleo-sorption. To extract plasmid DNA from E. coli cells PureLink Quick Plasmid DNA MiniprepKits were used. The presence of tcpACIRS gene was assayed by PCR, using designed through our own efforts primers. DNA fragments were isolated from agarose gel with the help of PCR Clear-Up-System panel. SDS-PAGE was performed according to U.K.Laemmli method. Protein content of samples was measured by M.M.Bradford method. The panel for affinity chromatography was applied for recombinant TcpA protein purification. Results and conclusions. Constructed safe strain of E. coli is the producer of recombinant TcpA protein, basic subunit of toxin-coregulated pilus of adhesion of cholera agent biovar El Tor. The region of tcpA gene of Vibrio cholerae biovar El Tor was cloned as part of vector plasmid pET302 by the restriction sites XhoI-BamHI in E. coli strain BL21(DE3)Star. In the stated design protein biosynthesis is under transcriptional control of phage promoter T7 and induced by isopropyl-ß-thiogalactoside (IPTG). Tested were the conditions for optimum TcpA protein production and the layout of its purification using affinity chromatography. It was demonstrated that TcpA is present in cells of intestinal bacterium, both in native form and as inclusion bodies. Overall TcpA protein production amounted to 60 mcg/ml. Obtained purified TcpA protein can be used for studies of its immunogenic and physical-chemical properties, as well as development of immune-diagnostic preparations to evaluate the level of TcpA production in various V. cholerae strains, and identification of antigen composition of cholera vaccine preparations.